Inspiring designers : a sourcebook. - Rodgers, Paul Anthony, 1965- (London : Black Dog, 2004)
Inhoudsopgave : Ron Arad, Shin and Tomoko Azumi, Rowan and Erwan Bouroullec, Matali Crasset, Nick Crosbie, DUMoffice, Mark Dytham, Marti Guixe, Thomas Heatherwick, Scott Henderson, Ichiro Iwasaki, Hella Jongerius, RADI, Karim Rashid, Tejo Remy, Arnout Visser, Marcel Wanders, Tokujin Yoshioka
Keywords: Ontwerpers